Association of NT-proBNP in Patients of Heart Failure with Preserved Ejection Fraction - Ali Rizvi, Syed Murtaza; Khattak, Zahoor; Khan, Nadir; Waheed Ur Rehman; Gul, Jawad; Mumtaz, Zahid (Indus Journal of Bioscience Research, 2025)
Objective: To determine the association of different levels of N- terminal B-type natriuretic peptide in patients of heart failure with preserved ejection fraction. Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Cardiology, Armed Forces Institute of Cardiology Rawalpindi from August 06, 2024 to March 05, 2025. Methodology: A total of 368 patients between the age of 20-75 years belonging to both genders with the diagnosis of heart failure with preserved ejection fraction were included in the study. Patients who were obese, had deranged renal profile, atrial fibrillation, and chronic obstructive pulmonary disease were excluded. N- terminal B-type natriuretic peptide levels of all patients were documented and grades of diastolic dysfunction were ascertained. Data analysis was done using SPSS version 25 taking p value of <0.05 as statistically significant. Results: The mean age of patients included in the study was 61.4±11.8 years. There were 157 male patients (42.7%) while 211 patients (57.3%) were female. The mean value of NT-proBNP in patients below 50 years of age was 312.9±271.3 ng/L while the mean value for patients above the age of 50 years was 426.3±571.9 ng/L (p=0.075). The median threshold value in patients with diastolic dysfunction Grade I was 389 pg/L. A statistically significant relationship was found between the values of NT-proBNP and the grades of DD (p<0.001). Conclusion: N- terminal B-type natriuretic peptide is significantly associated with the degree of diastolic dysfunction in patients presenting with heart failure with preserved ejection fraction.